Kontribusi Zakat dan Wakaf Untuk Mencapai Tujuan Pembangunan Berkelanjutan: Solusi dalam Mengurangi Kesenjangan Sosial Ekonomi - Aini, Rija; Nasution, Yenni Samri Juliati (Regress: Journal of Economics & Management, 2024)
This article aims to analyze the strategic role of zakat and waqf in supporting the achievement of Sustainable Development Goals (SDGs) 10, which focuses on reducing social and economic inequality. This research uses a literature study approach to analyze literature and secondary data related to the implementation of zakat and waqf in reducing socio-economic inequality. The results show that Zakat functions as an instrument of wealth redistribution that directly targets underprivileged groups through consumptive assistance and productive zakat programs that empower mustahik to become economically independent so that it has an influence on reducing poverty and improving welfare. Meanwhile, waqf provides long-term contribution through financing the sustainable development of education, health, and social infrastructure facilities. In conclusion, zakat and waqf have great potential to support SDGs 10 by creating a more inclusive, just and prosperous society through sustainable reduction of socio-economic inequality.